The Role of Photography in Conceptual Art in Iranian Artists - Dianat, Fereshteh (Journal of History Culture and Art Research, 2017)
Abstract Conceptual art is one of the new independent art forms of modern times. Photography is one of the areas where this art form appears since it is always considered as a document and reflection of reality. As photography plays an essential role in the first conceptual artworks of Joseph Kossuth, this research questions “to what extend photography can play an essential role in conceptual artworks?” It was not very late after rise of conceptual art that Iran was in line with these new developments. Therefore, it is tried to study the role of photography in conceptual art through investigating Iranian artist’s art works. Here it is tried to review two main exhibitions of conceptual artworks held in contemporary art museum of Tehran during 2001 to 2002 as well as field study approaches about artworks in other galleries, to reveal the importance of photography in conceptual artwork. The present study attempts to define conceptual art beside a quick review of the first photos that apparently effected formation of conceptual art in Iranian artist’s artworks.